Nursing Care for the Discomfort Disorder in 'S' Diagnosed with Dyspepsia in the Sanur Room, Sumber Kasih Hospital, Cirebon City - Herlina Herlina; Pujiyana Pujiyana; Ira Rahayu Okta; Lalu Rahmatullah Hidayat; Ahmad Syaripudin (Al Makki Publisher, 2024)
Dyspepsia is a non-communicable disease that is common around the world, including Indonesia. This disease is often accompanied by discomfort or pain in the upper abdomen which can interfere with the patient's quality of life. This study aims to evaluate the effectiveness of nursing care in patients with dyspepsia diagnosis, especially in meeting the need for a sense of security and comfort through relaxation techniques. This study uses a qualitative method with a prospective case study approach. Data collection techniques include observation, interviews, and documentation studies, which are then comprehensively analyzed. The results showed that after 2x24 hours of nursing treatment with relaxation therapy in patient